Analysis and Research on the Characteristics of Historical Villages Based on Spatial Syntax - Junzhang Chen (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study takes Cuiwei village, located in Qianshan District of Zhuhai City, as an example. First, it analyzes the human flow activities and activity size of village road a, the visual agglomeration degree and the spatial characteristics of historical sections. Secondly, select the most representative traditional buildings in the village, namely Sanwang temple and Wechsler mansion. When r=n and radius r=3, observe the changes of two parameters of visual integration and visual depth of the two historical buildings. And with the help of Baidu time machine photos of different periods to observe and record the changes of stores and human behavior characteristics. The results show that at this stage, the coordination of villages is poor, people's recognition in the village space is weak, people can't use local perception to reflect the overall space, there is an obvious interface between the inside and outside of the village, the isolation state is obvious, the local intelligibility is good, but the global intelligibility is poor.